Comment lire le carnet de voyage scientifique au xviiie siècle ? - Nathalie Vuillemin (Viatica, 2018)
In the 18th century, naturalist travellers played a major role in the dissemination of information because they engaged in a variety of scholarly practices: logbooks, maps, drawings, herbariums, collection of objects and plants. Personal impressions are not at the forefront of the writing of the scholar-traveller; rather, it is full of concrete observations and results. However, Philibert Commerson’s journals also show a narrative approach that makes the naturalist doctor a potential writer.